Water-based soldering flux and preparation method thereof
By using fluorinated graphite oxide-loaded active agents in water-based flux, the problem of insufficient wetting and corrosion resistance of water-based flux is solved, and more efficient cleaning and corrosion-proof effects are achieved during welding.
Patent Information
- Application Number
- CN202411977684.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing water-based flux has poor wetting and corrosion resistance, making it difficult to meet the needs of efficient cleaning and corrosion protection during welding.
By using fluorinated graphite oxide-loaded rare earth oxide active agent in the aqueous flux, the wetting and corrosion resistance of the flux are improved. Fluorinated graphite oxide enhances surfactivity and dispersion by introducing oxidation groups, while rare earth oxides improve the corrosion resistance of the active agent.
It significantly improves the wetting and corrosion resistance of flux, improves the flowability and adhesion during welding, reduces the surface tension of the welded material, and improves the corrosion resistance of the welded seam.
Smart Images

Figure BDA0005220814530000081 
Figure BDA0005220814530000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of soldering flux, and more specifically, to a water-based soldering flux and a preparation method thereof. Background Art
[0002] Soldering is the main process in electronic assembly, and flux is an auxiliary material used in soldering. The main function of flux is to remove oxides on the surface of solder and the base material to be soldered, so that the metal surface reaches the necessary cleanliness. It prevents the surface from being oxidized again during soldering, reduces the surface tension of solder, and improves soldering performance. The quality of flux performance directly affects the quality of electronic products.
[0003] At present, most of the fluxes used are organic solvent-based fluxes. The active ingredients of this type of flux must be dissolved in organic solvents. When used, they have the disadvantages of high volatility, flammability, and harm to the body. Water-soluble flux uses deionized water as a solvent, which is environmentally friendly and safe, and can be well applied to PCB welding. However, the surfactant used in the active component of water-based flux has a single component, which makes the flux poor in improving wettability and corrosion resistance.
[0004] Therefore, improving the wettability and corrosion resistance of active components is of great significance to the development of water-based flux. Summary of the invention
[0005] In order to improve the wettability and corrosion resistance of water-based flux, the present application provides a water-based flux and a preparation method thereof.
[0006] In the first aspect, the present application provides a water-based flux, which adopts the following technical solution: A water-based soldering flux is made of the following raw materials in parts by weight: 4-8 parts of an activator, 6-12 parts of an organic solvent, 3-8 parts of an organic acid and 80-90 parts of deionized water; the activator is prepared by loading rare earth oxide on fluorinated graphite oxide.
[0007] By adopting the above technical solution, the fluorinated graphite oxide obtained by introducing active oxidizing groups in the fluorinated graphite in the activator has good surface activity and dispersibility, which can reduce the internal stress of the flux during welding, thereby improving the flow rate and adhesion of welding, improving the ability of the flux to improve wettability, and reducing the surface tension of the welded material; at the same time, graphite can improve the corrosion resistance of the weld after welding. Rare earth oxides have excellent corrosion resistance. By loading on fluorinated graphite oxide, they can not only prevent the fluorinated graphite from agglomerating, but also improve the corrosion resistance of the activator. That is, the present application can improve the wettability and corrosion resistance of the flux by adding an appropriate amount of activator to the water-based flux.
[0008] In a specific embodiment, the preparation method of the active agent comprises the following steps: Placing a concentrated sulfuric acid solution in an ice bath, adding 1 part by weight of graphite fluoride and 0.1 part by weight of graphite oxide, stirring and ultrasonicating, and then adding 3-15 parts by weight of an oxidant to react to obtain a fluorinated graphite oxide mixed solution; filtering and drying the fluorinated graphite oxide mixed solution to obtain fluorinated graphite oxide; The fluorinated graphite oxide is mixed with deionized water and a surfactant to form a dispersion, and then a mixed solution formed by a soluble rare earth salt solution and an alkaline solution in a molar ratio of 1:2-4 is added, and the mixed solution is subjected to a hydrothermal reaction to obtain the active agent.
[0009] By adopting the above technical scheme, on the one hand, by adding an appropriate amount of graphite oxide to the fluorinated graphite, the interaction of graphite sheets is enhanced by hydrogen bonding, and the film-forming property of the flux is improved. At the same time, the addition of an appropriate amount of graphite oxide can maintain the insulation of the film during the subsequent hydrothermal reaction; on the other hand, the fluorinated graphite is hydrophobic because many F atoms are grafted on the graphite. By using ultrasonic treatment, during the propagation of ultrasonic waves, the particles in the elastic medium vibrate and transfer energy along the propagation direction, thereby generating mechanical effects, thermal effects and acoustic cavitation phenomena. These phenomena are applied in the ultrasonic treatment process, which can not only depolymerize the fluorinated graphite powder particle aggregates in concentrated sulfuric acid, but also disperse the fluorinated graphite in concentrated sulfuric acid to obtain a dispersion with a relatively uniform particle size. The cavitation effect of ultrasonic waves can also be used to remove the air dissolved or retained in the fluorinated graphite powder, thereby facilitating the contact between concentrated sulfuric acid and fluorinated graphite, accelerating the infiltration process of concentrated sulfuric acid on fluorinated graphite, and facilitating the subsequent reaction. In addition, the cavitation effect of ultrasound can also penetrate the isolation layer covering the fluorinated graphite, promote the diffusion, intercalation and reaction of concentrated sulfuric acid into the fluorinated graphite, and the resulting fluorinated graphite oxide has more oxygen-containing groups, so it has higher activity and dispersibility. Furthermore, loading rare earth oxide nanoparticles on the fluorinated graphite oxide layer can not only prevent the fluorinated graphite from agglomerating and improve its dispersibility, but also improve the corrosion resistance of the prepared active agent due to the corrosion inhibition effect of rare earth oxide.
[0010] In a specific embodiment, the preparation method of the fluorinated graphite is: fluorination treatment of graphene powder with a mixed gas of fluorine and nitrogen is performed to obtain the fluorinated graphite.
[0011] By adopting the above technical solution, since nitrogen has little effect on temperature and plays a diluting role, nitrogen is introduced during fluorination treatment to make the heat exchange more complete after gas mixing, and the graphite is subjected to fluorination surface treatment to induce a surface medium chemical reaction. On the one hand, the high mechanical properties of the graphite itself can be maintained, and on the other hand, its dispersibility, wettability and corrosion resistance in the flux can be improved.
[0012] In a specific embodiment, the fluorine-to-carbon ratio of the fluorinated graphite is 1.1-1.3:1.
[0013] By adopting the above technical solution, if the fluorine-carbon ratio is too low, the thermal stability and lubrication performance of the fluorine-carbon graphite will be poor; while the fluorinated graphite with a high fluorine-carbon ratio is difficult to obtain, which increases the cost.
[0014] In a specific embodiment, the oxidant is potassium permanganate or a mixture of potassium permanganate and sodium nitrate.
[0015] By adopting the above technical scheme, potassium permanganate and sodium nitrate not only act as oxidants to introduce oxidizing groups into graphite fluoride to improve the activity and dispersibility of graphite fluoride; but also their excess potassium ions and sodium ions can reduce the melting point and surface tension of the flux, refine the molten droplets, and reduce the free spattering degree of the flux during the welding process.
[0016] In a specific embodiment, the surfactant is one or more of stearic acid, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium glycocholate; further, the surfactant is sodium dodecylbenzene sulfonate.
[0017] By adopting the above technical solution, sodium dodecylbenzene sulfonate has low surface tension, good wetting power, excellent foaming performance and high foam stability. Sodium dodecylbenzene sulfonate is neutral, not easy to oxidize, easy to compound with various additives, low cost, and mature synthesis process.
[0018] In a specific embodiment, the rare earth element in the soluble rare earth salt solution is one of Yb, Er, Sm, Eu, Y, Gd, Dy, and Ce; further, the rare earth element in the soluble rare earth salt solution is Ce.
[0019] By adopting the above technical scheme, rare earths have a strong affinity with sulfur and oxygen in the weld, generating spherical or ellipsoidal rare earth sulfides, oxides or oxygen-sulfur composite inclusions, which significantly improve the sulfide inclusions in the weld; and the density of the compound generated by rare earth cerium and sulfur and oxygen in the weld is about 6.0, which is easy to float and remove in the weld, so the flux containing rare earth cerium can maximize the corrosion resistance of the flux.
[0020] In a specific embodiment, the organic solvent is a mixture of a low boiling point (less than 100° C.) organic solvent, a medium boiling point (100-150° C.) organic solvent and a high boiling point (150-200° C.) organic solvent.
[0021] By adopting the above technical solution, the organic solvent plays a role of solubilizing in the flux, which can improve the solubility of the active agent in deionized water and the stability after dispersion. Low boiling point solvents are beneficial to preventing the sagging of the weld, and have the advantages of fast evaporation, easy drying and low viscosity; medium boiling point solvents are beneficial to the leveling of the weld to form a dense paint film after the low boiling point solvent evaporates; high boiling point solvents are beneficial to leveling and can prevent the weld from being damaged by humidity and low temperature. By combining organic solvents with different boiling points, their synergistic effect can be exerted to improve the stability and welding activity of the flux.
[0022] In a specific embodiment, the low boiling point organic solvent is ethanol, the medium boiling point organic solvent is butyl acetate, and the high boiling point organic solvent is ethylene glycol butyl ether; the mass ratio of ethanol, butyl acetate and ethylene glycol butyl ether is 2:(3-5):(3-5).
[0023] By adopting the above technical solution, the organic solvent is a combination of alcohol, ester and ether, which can gradually decompose or sublime as the welding process temperature continues to rise, effectively ensuring that the water-based flux plays a role in fluxing during the entire welding process, and can effectively reduce the content of welding residues; at the same time, by selecting three specific organic solvents and controlling their mass ratio, their solubility-assisting effect can be better exerted.
[0024] In a second aspect, the present application provides a method for preparing a water-based flux, which adopts the following technical solution: A method for preparing a water-based soldering flux comprises the following steps: Weigh corresponding weight portions of an organic solvent and a portion of deionized water and mix them to form a mixed solution; The active agent is mixed with the remaining amount of deionized water to form a mixture, and the mixture is mixed with the mixed liquid.
[0025] By adopting the above technical solution, the activator of the flux is mixed with deionized water as the activation part in the flux system and then mixed with the organic solvent, so that the beneficial effect of the activator can be maximized. The water-based flux prepared by the present application uses deionized water as a solvent, which reduces the production cost and achieves the purpose of environmental protection, stability and safety, and the added activator has the advantage of improving the wettability and corrosion resistance of the flux.
[0026] In summary, this application has the following beneficial effects: 1. In the present application, the active agent is formed by loading rare earth oxide on fluorinated graphite oxide. The fluorinated graphite oxide obtained by introducing oxidizing groups into the fluorinated graphite oxide has good surface activity and dispersibility, improves the fluidity and adhesion of welding, and makes the active agent have good wettability and corrosion resistance; at the same time, by loading rare earth oxide on the fluorinated graphite oxide, the corrosion resistance of the obtained active agent is further improved; 2. The organic solvent in this application is a mixture of a low-boiling point organic solvent, a medium-boiling point organic solvent and a high-boiling point organic solvent. As the temperature of the welding process continues to rise, the three gradually decompose or biodegrade, which can effectively ensure the fluxing effect of the water-based flux in the entire welding process. At the same time, it can effectively reduce the content of welding residues, achieve a synergistic effect, and improve the stability and corrosion resistance of the flux. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0028] Preparation Example 1 In this preparation example, the active agent was prepared according to the following method: (1) placing 0.5 g of graphene powder in a high-pressure reactor, introducing a mixed gas formed by fluorine gas and nitrogen gas in a volume ratio of 4:1 into the reactor, and fluorinating for 5 h at a pressure of 50 kPa and a temperature of 300° C. to obtain fluorinated graphene powder; (2) 30 ml of 98 wt% concentrated sulfuric acid solution was added to a flask, and the mixture was placed in an ice bath. Then, 1 g of the fluorinated graphene powder and 0.1 g of graphite oxide were added to the flask, magnetically stirred for 1 h, and then ultrasonically treated for 15 min, wherein the ultrasonic frequency was 55 kHz and the ultrasonic intensity was 0.9 W / cm2. The mixture was then placed in an ice bath and stirred for 30 min to form a mixed solution. 9 g of potassium permanganate solid was slowly added to the mixed solution, and magnetic stirring was continued for 3 h. The mixture was then placed in a water bath at 35°C for constant temperature treatment for 1 h to obtain a fluorinated graphite oxide mixed solution. A large amount of deionized water was added to the obtained fluorinated graphite oxide mixed solution, and the mixture was allowed to stand for stratification. The upper layer product was then washed at a centrifugal speed of 2000 r / min until the pH value of the solution was 7, and vacuum dried at 50°C for 60 h to obtain a fluorinated graphite oxide powder. The F:O was measured to be 1.2:1 by X-ray electron spectroscopy (XPS). (3) 30 mg of fluorinated graphite oxide powder was mixed with 70 mg of deionized water, sodium dodecylbenzene sulfonate was added and ultrasonicated for 3 h to disperse it into a suspension, and then 10 ml of 0.1 mg / ml cerium nitrate hexahydrate solution and 10 ml of 0.3 mol / ml ammonia water were mixed under magnetic stirring; the mixed solution was then transferred to a hydrothermal reactor and reacted at 220° C. for 24 h. Finally, the mixture was washed with ethanol and deionized water until neutral, and vacuum dried to obtain an active agent.
[0029] Preparation Example 2 In this preparation example, the active agent was prepared according to the following method: (1) placing 0.5 g of graphene powder in a high-pressure reactor, introducing a mixed gas formed by fluorine gas and nitrogen gas in a volume ratio of 3:1 into the reactor, and fluorinating for 2 h at a pressure of 10 kPa and a temperature of 300° C. to obtain fluorinated graphene powder; (2) Add 30 ml of 98 wt% concentrated sulfuric acid solution to a flask, place it in an ice bath, then add 1 g of the above-mentioned fluorinated graphene powder and 0.1 g of graphite oxide to the flask, stir magnetically for 1 hour, and then ultrasonically treat for 15 minutes, wherein the ultrasonic frequency is 55 kHz and the ultrasonic intensity is 0.9 W / cm2, then place it in an ice bath and continue stirring for 30 minutes to form a mixed solution; slowly add 3 g of potassium permanganate solid to the above-mentioned mixed solution, continue magnetic stirring for 3 hours, and then place it in a water bath at 35°C for constant temperature treatment for 1 hour to obtain a fluorinated graphite oxide mixed solution; add a large amount of deionized water to the obtained fluorinated graphite oxide mixed solution, let it stand for stratification, and then wash the upper layer product at a centrifugal speed of 2000 r / min until the solution pH value is 7, and vacuum dry it at 50°C for 60 hours to obtain a fluorinated graphite oxide powder, and the F:O=1.1:1 is measured by X-ray electron spectroscopy (XPS); (3) 30 mg of fluorinated graphite oxide powder was mixed with 70 mg of deionized water, sodium dodecylbenzene sulfonate was added and ultrasonicated for 2 h to disperse it into a suspension, and then 10 ml of 0.1 mg / ml cerium nitrate hexahydrate solution and 10 ml of 0.2 mol / ml ammonia water were mixed under magnetic stirring; the mixed solution was then transferred to a hydrothermal reactor and reacted at 200° C. for 20 h. Finally, the mixture was washed with ethanol and deionized water until neutral, and vacuum dried to obtain an active agent.
[0030] Preparation Example 3 In this preparation example, the active agent was prepared according to the following method: (1) placing 0.5 g of graphene powder in a high-pressure reactor, introducing a mixed gas of fluorine gas and nitrogen gas in a volume ratio of 5:1 into the reactor, and fluorinating for 8 h at a pressure of 100 kPa and a temperature of 500° C. to obtain fluorinated graphene powder; (2) 30 ml of 98 wt% concentrated sulfuric acid solution was added to a flask, and the flask was placed in an ice bath. Then, 1 g of the above-mentioned fluorinated graphene powder and 0.1 g of graphite oxide were added to the flask, magnetically stirred for 1 hour, and then ultrasonically treated for 15 minutes, wherein the ultrasonic frequency was 55 kHz and the ultrasonic intensity was 0.9 W / cm2. After that, the flask was placed in an ice bath and stirred for 30 minutes to form a mixed solution; 9 g of potassium permanganate and 5 g of sodium nitrate solid were slowly added to the above-mentioned mixed solution, and the mixture was magnetically stirred for 3 hours, and then placed in a water bath at 35°C for constant temperature treatment for 1 hour to obtain a fluorinated graphite oxide mixed solution; a large amount of deionized water was added to the obtained fluorinated graphite oxide mixed solution, and the mixture was allowed to stand for stratification, and then the upper layer product was washed at a centrifugal speed of 2000 r / min until the pH value of the solution was 7, and vacuum dried at 50°C for 60 hours to obtain a fluorinated graphite oxide powder, and F:O=1.3:1 was measured by X-ray electron spectroscopy (XPS); (3) 30 mg of fluorinated graphite oxide powder was mixed with 70 mg of deionized water, sodium dodecylbenzene sulfonate was added and ultrasonicated for 2 h to disperse it into a suspension, and then 10 ml of 0.1 mg / ml cerium nitrate hexahydrate solution and 10 ml of 0.4 mol / ml ammonia water were mixed under magnetic stirring; the mixed solution was then transferred to a hydrothermal reactor and reacted at 250° C. for 30 h. Finally, the mixture was washed with ethanol and deionized water until neutral, and vacuum dried to obtain an active agent.
[0031] Preparation Example 4 In this preparation example, the active agent was prepared according to the following method: (1) 0.5 g of graphene powder was placed in a high-pressure reactor, and a mixed gas formed by fluorine gas and nitrogen gas in a volume ratio of 4:1 was introduced into the reactor. The mixture was fluorinated at a pressure of 50 kPa and a temperature of 300° C. for 5 h to obtain fluorinated graphene powder.
[0032] Preparation Example 5 In this preparation example, the active agent was prepared according to the following method: (1) placing 0.5 g of graphene powder in a high-pressure reactor, introducing a mixed gas formed by fluorine gas and nitrogen gas in a volume ratio of 4:1 into the reactor, and fluorinating for 5 h at a pressure of 50 kPa and a temperature of 300° C. to obtain fluorinated graphene powder; (2) 30 ml of 98 wt % concentrated sulfuric acid solution was added to a flask and placed in an ice bath. Then 1 g of the above-mentioned fluorinated graphene powder and 0.1 g of graphite oxide were added to the flask, magnetically stirred for 1 hour, and then ultrasonically treated for 15 minutes, wherein the ultrasonic frequency was 55 kHz and the ultrasonic intensity was 0.9 W / cm2. Then, the flask was placed in an ice bath and stirred for 30 minutes to form a mixed solution. 9 g of potassium permanganate solid was slowly added to the above-mentioned mixed solution, and magnetic stirring was continued for 3 hours. Then, the mixed solution was placed in a water bath at 35° C. and treated at a constant temperature for 1 hour to obtain a fluorinated graphite oxide mixed solution. A large amount of deionized water was added to the obtained fluorinated graphite oxide mixed solution, and the mixture was allowed to stand for stratification. Then, the upper layer product was washed at a centrifugal speed of 2000 r / min until the pH value of the solution was 7, and vacuum dried at 50° C. for 60 hours to obtain a fluorinated graphite oxide powder. F:O=1.2:1 was measured by X-ray electron spectroscopy (XPS).
[0033] Preparation Example 6 In this preparation example, the active agent was prepared according to the following method: (1) placing 0.5 g of graphene powder in a high-pressure reactor, introducing a mixed gas formed by fluorine gas and nitrogen gas in a volume ratio of 4:1 into the reactor, and fluorinating for 5 h at a pressure of 50 kPa and a temperature of 300° C. to obtain fluorinated graphene powder; (2) 30 mg of graphite fluoride powder was mixed with 70 mg of deionized water, sodium dodecylbenzene sulfonate was added and ultrasonicated for 3 h to disperse it into a suspension, and then 10 ml of 0.1 mg / ml cerium nitrate hexahydrate solution and 10 ml of 0.3 mol / ml ammonia water were mixed under magnetic stirring; the mixed solution was then transferred to a hydrothermal reactor and reacted at a temperature of 220° C. for 24 h. Finally, the mixture was washed with ethanol and deionized water until neutral, and vacuum dried to obtain an active agent. Example
[0034] Example 1 In this embodiment, the water-based flux includes the following components: 6Kg of activator, 9Kg of organic solvent (1.8Kg of ethanol + 3.6Kg of butyl acetate + 3.6Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 85Kg of deionized water, wherein the activator is obtained by Preparation Example 1.
[0035] In this embodiment, the water-based flux is prepared according to the following steps: (1) Weighing corresponding weight portions of ethanol, butyl acetate and ethylene glycol butyl ether, mixing them evenly, and stirring and mixing them evenly with half the weight of deionized water to form a mixed solution; (2) Weighing a corresponding amount of active agent and the other half amount of deionized water, stirring and mixing to form a mixture; (3) The mixed liquid and the mixture are stirred and mixed evenly.
[0036] Example 2 The difference between this embodiment and embodiment 1 is that the active agent is obtained from preparation example 2.
[0037] Example 3 The difference between this embodiment and embodiment 1 is that the active agent is obtained from preparation example 3.
[0038] Example 4 The difference between this embodiment and embodiment 1 is that, in this embodiment, the water-based flux includes the following components: 4Kg of activator, 6Kg of organic solvent (1.2Kg of ethanol + 2.4Kg of butyl acetate + 2.4Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 90Kg of deionized water, wherein the activator is obtained by Preparation Example 1.
[0039] Example 5 The difference between this embodiment and embodiment 1 is that, in this embodiment, the water-based flux includes the following components: 8Kg of activator, 12Kg of organic solvent (1.2Kg of ethanol + 2.4Kg of butyl acetate + 2.4Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 80Kg of deionized water, wherein the activator is obtained by Preparation Example 1.
[0040] Example 6 The difference between this embodiment and embodiment 1 is that, in this embodiment, the water-based flux includes the following components: 6Kg of activator, 9Kg of organic solvent (1.8Kg of ethanol + 2.7Kg of butyl acetate + 4.5Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 85Kg of deionized water, wherein the activator is obtained by Preparation Example 1.
[0041] Example 7 The difference between this embodiment and embodiment 1 is that, in this embodiment, the water-based flux includes the following components: 6Kg of activator, 9Kg of organic solvent (1.8Kg of ethanol + 4.5Kg of butyl acetate + 2.7Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 85Kg of deionized water, wherein the activator is obtained by Preparation Example 1.
[0042] Comparative Example Comparative Example 1 In this comparative example, the water-based flux includes the following components: 6Kg of activator, 9Kg of organic solvent (1.8Kg of ethanol + 3.6Kg of butyl acetate + 3.6Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 85Kg of deionized water, wherein the activator is obtained from Preparation Example 4.
[0043] Comparative Example 2 In this comparative example, the water-based flux includes the following components: 6Kg of activator, 9Kg of organic solvent (1.8Kg of ethanol + 3.6Kg of butyl acetate + 3.6Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 85Kg of deionized water, wherein the activator is obtained from Preparation Example 5.
[0044] Comparative Example 3 In this comparative example, the water-based flux includes the following components: 6Kg of activator, 9Kg of organic solvent (1.8Kg of ethanol + 3.6Kg of butyl acetate + 3.6Kg of ethylene glycol butyl ether), 5Kg of hydroxysuccinic acid and 85Kg of deionized water, wherein the activator is obtained from Preparation Example 6.
[0045] Performance testing methods 1. Corrosion resistance test A 0.2mm×40mm×40mm PCB board was used as a welding board, the solder was Sn99.3Cu0.7, and the flux used was the one in each embodiment and comparative example. The welding board was welded with the solder and flux. After welding, the number and volume of pores on each board were counted. The test results are shown in Table 1.
[0046] 2. Wettability The metal sheet sample is immersed in the molten solder, and the load curve during lifting is measured. The wetting time and the wetting force corrected by buoyancy are obtained based on the load curve. The wetting force refers to the combined force of the force applied to the sample when it is vertically immersed in the molten solder and the buoyancy during immersion. The metal sheet sample used is a copper sheet (brand T2) with a specification of 10mm×30mm×0.3mm. The copper sheet sample is pretreated according to the method of "GB / T223.32-2008". Sn99.3Cu0.7 lead-free solder is used in the solder tank, the test temperature is 270℃, the speed is 5mm / s, the immersion depth is 7mm, and the holding time is 10s. The test results are shown in Table 1.
[0047] Table 1 Performance test data of Examples 1-7 and Comparative Examples 1-3 Combining Examples 1-7 and Comparative Example 1 and Table 1, it can be seen that when the water-based flux of Examples 1-7 is used for welding, its corrosion resistance and wettability are better than those of Comparative Example 1, indicating that the water-based flux prepared by the present application uses deionized water as a solvent, reduces production costs, achieves the purpose of environmental protection, stability and safety, and the added activator has the advantages of improving the wettability and corrosion resistance of the flux. In particular, the activator of the present application is loaded with rare earth oxides through fluorinated graphite oxide, has high welding activity, can effectively prevent oxidation, and improves the wetting effect of the flux on the material to be welded, reducing the surface tension of the material to be welded.
[0048] It can be seen from Example 1 and Comparative Example 2 and Table 1 that the present application forms an activator by further combining the fluorinated graphite oxide with a rare earth oxide. The rare earth oxide has good corrosion resistance. The rare earth oxide nanoparticles are loaded on the fluorinated graphite oxide layer, which can not only prevent the fluorinated graphite from agglomerating and improve its dispersibility, but also improve its uniformity in the activator, thereby improving the corrosion resistance and wettability of the flux acted by the activator.
[0049] Combining Example 1 and Comparative Example 3 with Table 1, it can be seen that the present application oxidizes the fluorinated graphite and then loads the rare earth oxide, and the fluorinated graphite has hydrophobicity due to the grafting of many F atoms on the graphite. The present application uses ultrasonic treatment to treat the fluorinated graphite and introduces oxygen-containing groups, so that the fluorinated graphite oxide has higher activity and dispersibility than the fluorinated graphite, and can improve the wettability and corrosion resistance of the active agent prepared therefrom.
[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A water-based flux, characterized in that: The invention comprises the following raw materials in parts by weight: 4-8 parts of an active agent, 6-12 parts of an organic solvent, 3-8 parts of an organic acid and 80-90 parts of deionized water; the active agent is prepared by loading rare earth oxide on fluorinated graphite oxide.
2. The water-based soldering flux according to claim 1, characterized in that: The preparation method of the active agent comprises the following steps: Placing a concentrated sulfuric acid solution in an ice bath, adding 1 part by weight of graphite fluoride and 0.1 part by weight of graphite oxide, stirring and ultrasonicating, and then adding 3-15 parts by weight of an oxidant to react to obtain a fluorinated graphite oxide mixed solution; filtering and drying the fluorinated graphite oxide mixed solution to obtain fluorinated graphite oxide; The fluorinated graphite oxide is mixed with deionized water and a surfactant to form a dispersion, and then a mixed solution formed by a soluble rare earth salt solution and an alkaline solution in a molar ratio of 1:2-4 is added, and the mixed solution is subjected to a hydrothermal reaction to obtain the active agent.
3. The water-based soldering flux according to claim 2, characterized in that: The preparation method of the fluorinated graphite is: using a mixed gas of fluorine and nitrogen to fluorinate graphene powder to obtain the fluorinated graphite.
4. The water-based soldering flux according to claim 3, characterized in that: The fluorine-carbon ratio of the fluorinated graphite is 1.1-1.3:
1.
5. The water-based soldering flux according to claim 2, characterized in that: The oxidant is potassium permanganate or a mixture of potassium permanganate and sodium nitrate.
6. The water-based soldering flux according to claim 2, characterized in that: The surfactant is one or more of stearic acid, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium glycocholate.
7. The water-based soldering flux according to claim 2, characterized in that: The rare earth element in the soluble rare earth salt solution is one of Yb, Er, Sm, Eu, Y, Gd, Dy, and Ce.
8. The water-based soldering flux according to claim 1, characterized in that: The organic solvent is a mixture of a low boiling point (less than 100° C.) organic solvent, a medium boiling point (100-150° C.) organic solvent and a high boiling point (150-200° C.) organic solvent.
9. The water-based soldering flux according to claim 7, characterized in that: The low boiling point organic solvent is ethanol, the medium boiling point organic solvent is butyl acetate, and the high boiling point organic solvent is ethylene glycol butyl ether; the mass ratio of the ethanol, butyl acetate and ethylene glycol butyl ether is 2:(3-5):(3-5).
10. The method for preparing the water-based flux according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh corresponding weight portions of an organic solvent and a portion of deionized water and mix them to form a mixed solution; The active agent is mixed with the remaining amount of deionized water to form a mixture, and the mixture is mixed with the mixed liquid.
Citation Information
Patent Citations
Leadless rosin core low-halogen no-clean scaling powder and method for preparing same
CN101543943A
Molecular environment-friendly heat-release welding agent applicable to welding of copper conductor
CN101745756A
Novel environmental-protection flux
CN105583550A
DE2137329A1
Fluorinated graphene oxide and method for producing the same
JP2018076196A